2015
DOI: 10.1097/mao.0000000000000604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Body Tilt on Multifrequency Admittance Tympanometry

Abstract: Changes in inner ear fluid pressure caused by body tilt induced an increase in the width of G tympanograms. In the vertical position, the mean value was 141.7 ± 56.5 daPa; in the supine position, it increased to 158 ± 58.3 daPa; and increased even more in the Trendelenburg position (20 degrees), with a mean of 184 ± 69.6 daPa (p < 0.01). Resonance frequency also increased in the Trendelenburg position.We conclude that the increased width of G tympanograms in MD patients outside an attack may be caused by an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…The latter could cause a pressure change in inner-ear fluids and alter the polarisation state of cochlear and vestibular hair cells, thereby contributing to symptoms of ear fullness, tinnitus, subjective hearing loss and vertigo 37 39 Subtle changes in inner-ear fluid pressure have been detected by multiple frequency tympanometry 40 …”
Section: Discussionmentioning
confidence: 99%
“…The latter could cause a pressure change in inner-ear fluids and alter the polarisation state of cochlear and vestibular hair cells, thereby contributing to symptoms of ear fullness, tinnitus, subjective hearing loss and vertigo 37 39 Subtle changes in inner-ear fluid pressure have been detected by multiple frequency tympanometry 40 …”
Section: Discussionmentioning
confidence: 99%
“…Also, MD patients compared to controls revealed a decrease in the RF [Franco-Vidal et al, 2005;Lilly, 1984]. Study findings were validated as Franco-Vidal et al demonstrated a reproducible increase of the inner ear pressure in normal subjects (by body tilts, Trendelenburg) with a concomitant increase of the G width [Franco-Vidal et al, 2015]. However, body tilt increased the RF.…”
Section: Introductionmentioning
confidence: 56%
“…Franco-Vidal et al [21] conducted multifrequency tympanometry for the Trendelenburg position and found the RF to be high. Although they could not give the exact reason for this, they suggested that there might be tension in the annular ligament due to the mass effect of increased inner-ear pressure generated by the position.…”
Section: Discussion/conclusionmentioning
confidence: 99%